Interaction of mass media with the audience in the context of convergence - Rassyhovich Gazizov, Ramis; Sergeevna Yufereva, Anastasia (Opción, 2019)
The article focuses on communicative convergence, which involves the process of the audience and periodicals role change in the information and communication space via comparative qualitative research methods. As a result, despite the significant increase of information on the Internet, most professional journalists are convinced that they have retained the right to retain the monopoly on information. The respondents came to this conclusion, based on the fact that journalists have all the necessary skills and competencies that allow them to engage in journalistic activities, while other users, in particular, bloggers, do not have the necessary qualities